DEVELOPMENT OF DIAGNOSTIC TEST: MATHEMATICAL MISCONCEPTION ON THE TOPIC OF NUMBER AND ALGEBRA FOR THE SEVENTH GRADE STUDENTS IN EAST LOMBOK - Zarkasi, Zarkasi; Sugiman, Sugiman (Jurnal Pendidikan Matematika dan IPA, 2019)
This study aims to: (1) look for the highest and lowest values in number and algebraic material of Junior High School in East Lombok, (2) the percentage of errors made by students when answering math problems, and (3) the diagnosis of student"™s misconception in doing number and algebra at Junior High School in East Lombok. This research is a quantitative- descriptive research. For the sampling technique, this study used purposive sampling. The test was conducted in five classes with 200 students as research participants. The sampling took into account the level of students"™ ability and school readiness. The sampling size is 361 students from five schools. The data were in the form of students"™ responses and those were analyzed using the Quest program. The results of this study are as follows. First, in terms of the difficulty index, 40 items (47%) are easy category items, 8% are medium category items, and 45% are difficult category items. Out of the 40 problems, 82% of the items have good difficulty index, while 18% are not good. Of the four alternative answers, 88% of the distractor is in a good category, and 12% are not good. Second, based on the students"™ answers, the percentage of error is 52 %. Third, based on the result of the analysis using the Quest program, of the tow materials, the biggest misconception is in number with the percentage of 68%. The dominant error is in the indicator representing fractions in various forms, with a percentage of 22%.